2016
DOI: 10.1007/s10926-016-9673-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Multidisciplinary Guideline for Low Back Pain: Process-Evaluation Among Health Care Professionals

Abstract: Background To reduce the burden of low back pain (LBP) in the Netherlands, a multidisciplinary guideline for LBP has been implemented in Dutch primary care using a multifaceted implementation strategy targeted at health care professionals (HCPs) and patients. The current paper describes the process evaluation of the implementation among HCPs. Methods The strategy aimed to improve multidisciplinary collaboration and communication, and consisted of 7 components. This process evaluation was performed using the Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…This means that to achieve successful implementation of RTW programs for cancer survivors, first awareness in each system needs to be raised and improved before the next implementation phase can be undertaken. This could, for instance, be achieved in the workplace system by means of management commitment and training/coaching activities for supervisors [19, 32], and in the healthcare and workplace systems simultaneously by means of interactive and multidisciplinary training sessions for healthcare professionals (physicians, specialised nurses, and occupational physicals) to create mutual understanding of each other’s discipline and perspective [33]. Additionally, in the societal system this could be achieved by means of providing information by the national government or the national cancer society or leading cancer charities about the possibilities to work after cancer via a national multimedia campaign, which has been done successfully by the UK charity organisation MacMillan [34].…”
Section: Discussionmentioning
confidence: 99%
“…This means that to achieve successful implementation of RTW programs for cancer survivors, first awareness in each system needs to be raised and improved before the next implementation phase can be undertaken. This could, for instance, be achieved in the workplace system by means of management commitment and training/coaching activities for supervisors [19, 32], and in the healthcare and workplace systems simultaneously by means of interactive and multidisciplinary training sessions for healthcare professionals (physicians, specialised nurses, and occupational physicals) to create mutual understanding of each other’s discipline and perspective [33]. Additionally, in the societal system this could be achieved by means of providing information by the national government or the national cancer society or leading cancer charities about the possibilities to work after cancer via a national multimedia campaign, which has been done successfully by the UK charity organisation MacMillan [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is arguable that the participating patients were in good health states from the start and gaining much improvement on these functional outcomes was not realistic. Process evaluations among participating patients and professionals alongside the present study showed that compliance with the intervention was very low 20 21. Most patients did not comply to the full eHealth intervention: 31% of the participants had not used the campaign materials at all, and 42.9% had only used it once, and professionals almost never discussed the intervention with their patients.…”
Section: Discussionmentioning
confidence: 66%
“…Most patients did not comply to the full eHealth intervention: 31% of the participants had not used the campaign materials at all, and 42.9% had only used it once, and professionals almost never discussed the intervention with their patients. Probably most participants did not need the intervention to improve their functional ability, but improvement in back pain beliefs could have been possible had the compliance rates in this study been higher 20 21…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These evaluations are essential to better understand how interventions can be integrated into practice in the future. Process evaluations can provide valuable insights about why interventions are successful or not, why they are adopted into practice or not and to assist with future intervention strategies (Suman, Schaafsma, Buchbinder, van Tulder & Anema, 2017). For this pilot study, it was important to evaluate whether health professionals viewed the intervention as a short-term add-on activity or not, and to establish how older participants accepted and adopted the intervention (Jones, McKevitt, Riazi, & Liston, 2017).…”
Section: Approaches To Process Evaluationmentioning
confidence: 99%